2019
DOI: 10.12691/ajmcr-7-12-4
|View full text |Cite
|
Sign up to set email alerts
|

Partial Currarino Syndrome in Adulthood Mistaken for a Simple Presacral Mass

Abstract: Currarino syndrome is a rare congenital disease and its appearance in adulthood is exceptional. It is neglected in the typical differential diagnosis of a presacral mass. This results in severe complications following simple mass resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Literature review demonstrated additional cases of meningitis in patients with Currarino syndrome, many of which were due to fistulous connections between bowel and the anterior meningocele. A previous study reported an enterothecal fistula in an adult patient as an acute complication following sacral mass resection; however, this patient was found to have undiagnosed partial Currarino syndrome ( 5 ). Across these studies, no general consensus was made on the method or timing, as some fistulas were treated medically, some with early surgery, and some with late surgery ( 6 - 10 ).…”
Section: Discussionmentioning
confidence: 79%
“…Literature review demonstrated additional cases of meningitis in patients with Currarino syndrome, many of which were due to fistulous connections between bowel and the anterior meningocele. A previous study reported an enterothecal fistula in an adult patient as an acute complication following sacral mass resection; however, this patient was found to have undiagnosed partial Currarino syndrome ( 5 ). Across these studies, no general consensus was made on the method or timing, as some fistulas were treated medically, some with early surgery, and some with late surgery ( 6 - 10 ).…”
Section: Discussionmentioning
confidence: 79%